Talak di Luar Pengadilan dalam Perspektif Fatwa Mui No. 4 Tahun 2012, Undang-Undang Perkawinan dan Kompilasi Hukum Islam - Andriansyah, Andriansyah; Winarno, Winarno; Ismanto, Reno (Fakultas Syariah dan Ekonomi Islam, IAIN Syaikh Abdurrahman Siddik, Bangka Belitung, 2025)
Divorce (ṭalāq) is a husband's right to terminate a marriage, based on the Qur'an and Hadith. However, the technical procedures for pronouncing divorce—particularly when declared outside the court—are not explicitly regulated in these primary sources, leading to differing views among the public. In response, the Indonesian Council of Ulama (Majelis Ulama Indonesia, MUI) issued Fatwa No. 4 of 2012, declaring that extrajudicial divorce is religiously valid but must be verified in court proceedings, with the wife’s waiting period (iddah) calculated from the moment the husband declares the divorce. This study employs a library research method, utilizing primary legal sources such as Fatwa No. 4/2012, the Indonesian Marriage Law, and the Compilation of Islamic Law (KHI), with data collected through documentation and analyzed using descriptive analysis. The results show, first, that according to MUI's fatwa, divorce outside the court is valid under Islamic law. Second, this fatwa contradicts the formal legal system in Indonesia, particularly Article 39 of the Marriage Law and Article 115 of the KHI, both of which stipulate that divorce—whether by ṭalāq or judicial petition—must be carried out before a court session to be legally recognized. Therefore, the MUI fatwa cannot serve as a binding legal basis within the Indonesian legal framework.